Initial inequality and trajectories of human capital accumulation under two regimens of educational financing: Simulations for Colombia - Vivas Pacheco, Harvy (Sociedad y Economía, 2016)
This paper studies the dynamic relationship between local socioeconomic environment,initial inequality in family incomes and impacts on the trajectories of accumulation ofhuman capital in Colombia. The study compares the dynamic trajectories of a centralizedfinancing system of education services, and a decentralized system in which educationalcosts are financed with local resources or with own resources of families. The study resultssuggest that when there is an initial severe heterogeneity in resourcing of families,in the long term an economic and social system with strong central government in thefinancing of education spending is more efficient than one in which the resources forthe provision of educational services come predominantly of own resources of familiesor from the tax rates to local rents.